(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the lexical-semantic features of euphemisms in the Karakalpak language, their sources of formation and thematic usage. The semantic nature of euphemisms, their semantic transformations and communicative functions are analyzed. Euphemistic units found in Mahmud Kashgari’s “Dīwān Lughāt at-Turk” are compared with modern Karakalpak euphemisms. The study reveals that euphemisms are closely related to cultural values, religious beliefs and etiquette norms of the Karakalpak people. Thematic classifications of euphemisms are identified and their role in softening emotionally sensitive information in communication is demonstrated.